High temperature forming of boronized duplex stainless steel / Rosnaini Saidan - Rosnaini, Saidan (2015)
The purpose of this work is to study the forming effect of boronized duplex stainless steel (DSS) at high temperature. Pack-boronizing of treated-DSS was carried out at 1223 K for 2, 4 and 6 hours, resulting surface hardness that range between 1890 and 2418 HV. The effects of microstructure, strain rate and surface hardness on high temperature forming process of the boronized treated-DSS were investigated. The forming was also done to its counterpart, the untreated (as-received) DSS, as a controlling factor. The results showed that in general, boronizing increased the flow stress of the forming, as similarly, higher surface hardness also increased the flow stress of the forming. However, the flow stress of the boronized treated-DSS was significantly lower than that of the boronized as-received DSS and comparable to the flow stress of non-boronized as-received DSS, therefore the flow stress during the forming is not only affected by the surface hardness but also strongly affected by the original microstructure of the substrate. The much lower flow stress is attributed to the superplasticity brought about by the fine grain microstructure of the treated-DSS. The study also concluded that with slower strain rate, the surface integration of the boronized treated-DSS can be maintained even though the hardness of the boronized treated DSS is relatively high.